Role of Public-Private Partnership in School Resource Management - Atoyin, Victor Mifa Cassidy; Atte, Temitope Priscilla (International Journal of Educational Management, 2021)
This study examined the role of public-private partnership in school resource management in senior secondary schools in Federal Capital Territory, Abuja. Research design adopted was descriptive survey. Questionnaires was the instrument used for data collection. Mean score, standard deviation and Pearson ProductMoment Correlation aided data analysis. Finding revealed that the extent of school resource management in senior secondary schools in Federal Capital Territory, Abuja is high; the role of public-private partnership in school resource management incudes human resources management, material resources management, physical resources management through efficient cost saving mechanism, prudent financial resources management for improved service delivery and adequate information resources organization for efficient decision making. The recommendations proposed are that more efforts should be geared towards ensuring that school resource management is continually improved upon so that the high tempo recorded can be kept at that level instead of relaxing without putting efforts to improve the current existing relationship between the government and private bodies; and government as well as private bodies should not relent in its functional roles of human resources management, material resources management, physical resources management, prudent financial resources management for improved service delivery and adequate information resources organization for efficient decision making so that such roles can continue to bring about realization of set goals and objectives of secondary education in FCT.